Prospective case control study of iron deficiency and the risk of febrile seizures in children in South Korea - Han Na Jang; Hoi Soo Yoon; Eun Hye Lee (BMC, 2019)
Abstract Background Febrile seizures are the most common type of seizure in the first 5 years of life, and many factors that increase seizure risk have been identified. This study was performed to examine the association between iron status and febrile seizures in children in South Korea. Methods A prospective unmatched case control study was performed in 63 cases of febrile seizures and 65 controls with febrile illness but no seizures. Results Serum iron, plasma ferritin, and transferrin saturation were significantly lower in children with febrile seizures compared to the controls. Iron deficiency, defined as ferritin < 30 ng/mL, was more prevalent in the febrile seizure group (49.2%) than in the control group (16.9%). Serum iron < 22 ng/dL (odds ratio 3.42, 95% confidence interval [CI] 1.31-8.9, P = 0.012) and ferritin < 30 ng/mL (odds ratio 6.18, 95% CI 2.32-16.42, P < 0.001) were associated with increased risk of developing febrile seizures in multivariate logistic regression analysis. Conclusion These observations suggest that iron deficiency prior to development of anemia may increase risk of febrile seizures.